Why Locke’s “Of Power” Is Not a Metaphysical Pronouncement: Locke’s Response to Molyneux’s Critique - Marko, Jonathan S. (Philosophy & theology, 2017)
It is my contention here that the chapter “Of Power,” in John Locke’s An Essay Concerning Human Understanding, is not a metaphysical pronouncement upon the liberty-necessity debates but more along the lines of what those like James Harris portray it to be: a description of our experience of freedom of the will. It is also prescriptive since it is descriptive of the right use of the will. My claims are based upon two key pieces of evidence that are responses to William Molyneux’s oft noted critique of the first edition of the chapter: 1) an admission by Locke in his correspondence: at least part of the reason he is attempting to avoid metaphysical pronouncements is that trying to reconcile divine and human agency is too difficult; and 2) the theological message of “Of Power”—the truly free agent is reasonable, and the truly reasonable agent will have her eyes fixed on the afterlife, thus aiming for herself to be a slave and determined, therefore, by her ever-cultivated desire for righteousness and not by her fleshly desires—and his development of it throughout the chapter eludes sectarian categorization by the avoidance of theological issues that are not unrelated to the metaphysical question of human free agency. To frame his chapter otherwise makes him out to be a theological novice or, perhaps, unconcerned with the religious background of his readership.